Charting the way forward to better quality health care: how do we get there and what are the next steps? : Recommendations from the Salzburg Global Seminar on making health care better in low- and middle-income economies - Massoud, M. Rashad; Sax, Sylvia (International journal for quality in health care, 2012)
AbstractObjective. In April 2012, the Salzburg Global Seminar (SGS) brought together 58 health leaders from 33 countries to review experiences in improving the